Framework of an algorithm-aided BIM approach for modular residential building information models. (December 2022) - Pibal, Sophia S.; Khoss, Konstantin; Kovacic, Iva
The digital transformation of the construction industry and the lack of integration of digital technologies in design and construction processes are the motivation for this research. BIM solutions enable new levels of design processes and provide platforms for computational design and novel approaches in the AEC industry. In computational design parametric, generative or algorithmic procedures are utilized to support, optimize, or replace manual processes. The combination of BIM and generative, parametric or algorithmic design forms a hybrid that aims to combine the advantages of both concepts and allows for generative design processes with the creation of BIM objects containing metadata. Along with the digital transformation and novel approaches in the AEC industry, modular construction aims to shift from mass production to mass customization and maximize opportunities for cost-effective, economical, and sustainable buildings. This paper addresses the approach of generating building information models using algorithm-aided design combined with BIM at an early design stage for modular multi-story residential buildings that are affordable and sustainable. In this study, we present the framework of an algorithm-aided BIM approach, from the concept of the generative algorithm to the evaluation approach and the proof of concept as the test of the framework.